NADPH oxidase inhibitor apocynin prevents atrial remodeling in alloxan-induced diabetic rabbits. (15th October 2016) - Qiu, Jiuchun; Zhao, Jianping; Li, Jian; Liang, Xue; Yang, Yajuan; Zhang, Zhiwei; Zhang, Xiaowei; Fu, Huaying; Korantzopoulos, Panagiotis; Liu, Tong; Li, Guangping
Abstract: Objectives: Diabetes mellitus (DM) is an independent risk factor for atrial fibrillation (AF). The role of the NADPH oxidase (NOX) signaling in the setting of DM and the potential benefits of apocynin on diabetic atrial remodeling remain unknown. Methods: Sixty Japanese rabbits were randomized into 3 groups as follows: Control group (Control, n = 20), alloxan-induced diabetic group (DM, n = 20) and apocynin-treated diabetic group (APO, n = 20). Rabbits in the APO group were orally administered apocynin (15 mg/kg/day) for 8 weeks. Serum malonaldehyde (MDA), superoxide dismutase (SOD) levels, and left atrial tissue NADPH oxidase (NOX) activities were measured. Isolated rabbit hearts were Langendorff perfused. Atrial refractory effective period (AERP), atrial effective refractory period dispersion (AERPD), interatrial conduction time (IACT) and vulnerability to AF were assessed. Atrial interstitial fibrosis was evaluated by Masson's trichrome staining. The protein expression of NF-κB, TGF-β, p38, P-p38, JNK, P-JNK, ERK and P-ERK was measured by Western blot analysis. Results: There were no significant differences regarding SBP, DBP, LVEDP and AERP in the three groups. Compared with the Control group, AF inducibility was increased in the DM group (46/450 vs. 5/450, P < 0.05), and markedly reduced by apocynin (46/450 vs. 12/450, P < 0.05). Apocynin also attenuated atrial structural remodeling in diabetic rabbits. Western-blot analysis indicated that apocynin reduced the DM-induced increased protein expression of TGF-β, NF-κB, P-p38, P-JNK, ERK and P-ERK. Conclusions: Apocynin, a NADPH oxidase inhibitor, prevents AF and attenuates atrial remodeling in alloxan-induced diabetic rabbits.